Sublethal heat stress-induced O-GlcNAcylation coordinates the Warburg effect to promote hepatocellular carcinoma recurrence and metastasis after thermal ablation. (10th October 2021) - Chen, Ye; Bei, Jiaxin; Liu, Mingyu; Huang, Jingjun; Xie, Lulu; Huang, Wensou; Cai, Mingyue; Guo, Yongjian; Lin, Liteng; Zhu, Kangshun
Abstract: The malignant transformation of residual hepatocellular carcinoma (HCC) cells after thermal ablation is considered as the main factor promoting postoperative HCC progression, which greatly limits the improvement of long-term survival, and at present there is no effective targeted therapeutic strategies. The Warburg effect is a metabolic feature correlated highly with malignant transformation (e.g. epithelial-to-mesenchymal transition [EMT]). Here, we showed that sublethal heat stress triggered a stronger Warburg effect of HCC cells, which contributed to the thermotolerance and invasion of HCC cells. Sublethal heat stress-induced O-GlcNAcylation was involved in this process. Such enhanced Warburg effect in HCC cells may be eliminated through O-GlcNAcylation inhibition, resulting in impaired thermotolerance and EMT, and thereby preventing tumor recurrence and metastasis of HCC-bearing mice after insufficient thermal ablation. Finally, we present evidence that sublethal heat stress-induced O-GlcNAcylation regulates the Warburg effect in HCC cells by promoting hypoxia-inducible factor 1α (HIF-1α) stability. In conclusion, the present study suggests that O-GlcNAcylation coordinates the Warburg effect to promote HCC progression after thermal ablation, which may serve as a novel potential target for controlling postoperative HCC recurrence and metastasis. Highlights: Hepatocellular carcinoma (HCC) cells show enhanced Warburg effect after sublethal heat stress. Sublethal heat stress-induced O-GlcNAcylation is involved in promoting the Warburg effect of HCC cells. Inhibiting O-GlcNAcylation prevents HCC recurrence and metastasis after insufficient thermal ablation. O-GlcNAcylation regulates the Warburg effect by promoting hypoxia inducible factor-1α (HIF-1α) stability.